Polysaccharides in Medicinal Applications - Dumitriu, Severian; Ed (MARCEL DEKKER, 1996)
Integrates the advances in polysaccharide chemistry and structure analysis, with the practical applications of polysaccharides in medicine and pharmacy, highlighting the role of glycoconjugates in basic biological processes and immunology. This title presents various developments in glycobiology and glycopathology.